1994
DOI: 10.4028/www.scientific.net/msf.157-162.1039
|View full text |Cite
|
Sign up to set email alerts
|

Texture Development of Strip Cast Ferritic Stainless Steel

Abstract: The textures and the mechanical properties of a strip cast, cold rolled and recrystallized ferritic stainless steel with 16% Cr have been investigated and compared to conventionally processed hot band. The strip cast initial material exposed three improvements. First, the textures were weaker and more homogeneous through the sheet thickness. Second, it revealed a higher Lankfort value and third, the complete elimination of the ridging phenomenon.Texturentwicklung von bandgegossenem ferritlschem Edelstahl. Die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…7 Cr and Si, increases [46,50]. Owing to its high Cr content, after some δ→γ transformation, the remaining δ-ferrite phase did not undergo any further phase transformation during cooling.…”
Section: Texture Componentsmentioning
confidence: 92%
“…7 Cr and Si, increases [46,50]. Owing to its high Cr content, after some δ→γ transformation, the remaining δ-ferrite phase did not undergo any further phase transformation during cooling.…”
Section: Texture Componentsmentioning
confidence: 92%
“…This advanced and energy-efficient technology has attracted significant attention and different strip-cast steels such as low carbon steel [7][8][9][10], stainless steel [11][12][13][14][15][16] and silicon steel [17][18][19][20][21][22][23][24][25] have been studied. The previous studies [11][12][13][14][15][16][17][18][19][20][21][22][23] indicated that the strip casting had texture advantage in manufacturing stainless steel and nonoriented silicon steel, resulting in excellent formability and magnetic properties. However, the texture requirement of grain oriented silicon steel is different from the non-oriented silicon steel and the microstructure and texture of as-cast grain oriented silicon strip are undesirable compared to the conventional hot-rolled sheet [25].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the novel advanced and energyefficient process, strip casting technology, provides a promising possibility to produce steel that eliminates continuous casting, high temperature reheating, and multi-pass hot rolling, adopted during conventional processing [12][13][14]. Strip casting progress has attracted significant attention to manufacture steels over the world and shows a great potential advantage in texture control over conventional process [15]. Most of the corresponding investigations focus on the fabrication technique of non-oriented or regular thickness GO silicon steel in the recent years [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%